Correction: A comparative study of graphene–hydrogel hybrid bionanocomposites for biosensing. Issue 6 (21st March 2015) - Burrs, S. L.; Vanegas, D. C.; Rong, Y.; Bhargava, M.; Mechulan, N.; Hendershot, P.; Yamaguchi, H.; Gomes, C.; McLamore, E. S.
<x xml:space="preserve">Abstract</x> Correction for 'A comparative study of graphene–hydrogel hybrid bionanocomposites for biosensing' by S. L. Burrs et al., Analyst, 2015, DOI: ; Web: 10.1039/c4an01788a.